Teamwork and Communication in Acute Care: A Teaching Resource for Health Practitioners - Neil Cowie; Kalyani Premkumar; Angela Bowen; Susan Kuling; Joann Kawchuk; Mike Rooney; Gary Morris; Mark Burbridge; Jocelyne Martel; Joanne Sivertson; David C. Campbell; Cyril Coupal; et al. (Association of American Medical Colleges, 2012)
Abstract The need for cesarean birth is sometimes so urgent that regional anesthesia techniques such as spinal or epidural cannot be done quickly enough to safely deliver the baby. Primary general anesthesia for surgery is a rare event on the labor and birth unit, but is the only way in which cesarean birth can occur without jeopardizing the health and safety of the baby and/or mother. While this represents a small number of patients overall (10-12 per year in the authors' unit), the outcome can be devastating for both mother and baby when this procedure is not well managed. The purpose of this resource is to improve patient safety and quality of care for patients who must have an emergency cesarean birth under primary general anesthesia. This quality improvement resource emphasizes teamwork and communication in the labor and birth unit during these critical and emergent times through a series of videos depicting a pregnant woman requiring emergency cesarean birth under general anesthesia. This web-based and interactive video format is used as a clinical example that emphasizes the importance of teamwork and communication in an interdisciplinary acute care setting. Further, it is the authors hope that engagement with these videos will provoke an emotional involvement that will prime the learner to more actively participate in other medical education exercises such as debriefings after medical simulations.